Mapping Functional Interaction Sites of Human Prune C‐Terminal Domain by NMR Spectroscopy in Human Cell Lysates. Issue 37 (12th August 2013) - Diana, Donatella; Smaldone, Giovanni; De Antonellis, Pasquale; Pirone, Luciano; Carotenuto, MariaNeve; Alonzi, Alessandro; Di Gaetano, Sonia; Zollo, Massimo; Pedone, Emilia M.; Fattorusso, Roberto
<x xml:space="preserve">Abstract</x> Get well prune: The C‐terminal third domain of h‐prune is largely unfolded and involved in relevant protein–protein interactions, particularly with Nm23‐H1 (see figure), GSK‐3β and gelsolin. This study shows that protein functions mediated by protein–protein interactions can be accurately followed in cell lysates by using fast NMR spectroscopy, which could be easily used for a very efficient NMR drug‐discovery strategy.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>